Stream Ecosystem Functioning in an Agricultural Landscape - Hladyz, Sally; Åbjörnsson, Kajsa; Chauvet, Eric; Dobson, Michael; Elosegi, Arturo; Ferreira, Verónica; Fleituch, Tadeusz; Gessner, Mark O.; Giller, Paul S.; Gulis, Vladislav; Hutton, Stephen A.; Lacoursière, Jean O.; et al. (Advances in Ecological Research, 2011)
The loss of native riparian vegetation and its replacement with non-native species or grazing land for agriculture is a worldwide phenomenon, but one that is prevalent in Europe, reflecting the heavily-modified nature of the continent's landscape. The consequences of these riparian alterations for freshwater ecosystems remain largely unknown, largely because bioassessment has traditionally focused on the impacts of organic pollution on community structure. We addressed the need for a broader perspective, which encompasses changes at the catchment scale, by comparing ecosystem processes in woodland reference sites with those with altered riparian zones. We assessed a range of riparian modifications, including clearance for pasture and replacement of woodland with a range of low diversity plantations, in 100 streams to obtain a continental-scale perspective of the major types of alterations across Europe. Subsequently, we focused on pasture streams, as an especially prevalent widespread riparian alteration, by characterising their structural (e.g. invertebrate and fish communities) and functional (e.g. litter decomposition, algal production, herbivory) attributes in a country (Ireland) dominated by this type of landscape modification, via field and laboratory experiments. We found that microbes became increasingly important as agents of decomposition relative to macrofauna (invertebrates) in impacted sites in general and in pasture streams in particular. Resource quality of grass litter (e.g., carbon : nutrient ratios, lignin and cellulose content) was a key driver of decomposition rates in pasture streams. These systems also relied more heavily on autochthonous algal production than was the case in woodland streams, which were more detrital based. These findings suggest that these pasture streams might be fundamentally different from their native, ancestral woodland state, with a shift towards greater reliance on autochthonous-based processes. This could have a destabilizing effect on the dynamics of the food web relative to the slower, detrital-based pathways that dominate in woodland streams.